2020
DOI: 10.1002/jcp.29419
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tRNA‐derived small RNA (tsRNA) responsive to the tumor suppressor, RUNX1, in breast cancer

Abstract: Despite recent advances in targeted therapies, the molecular mechanisms driving breast cancer initiation, progression, and metastasis are minimally understood. Growing evidence indicate that transfer RNA (tRNA)‐derived small RNAs (tsRNA) contribute to biological control and aberrations associated with cancer development and progression. The runt‐related transcription factor 1 (RUNX1) transcription factor is a tumor suppressor in the mammary epithelium whereas RUNX1 downregulation is functionally associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 23 publications
(56 reference statements)
1
49
0
Order By: Relevance
“…57 The regulation of type II tsRNA biogenesis has only recently started to be revealed. Farina et al 58 determined that four type II tsRNAs (ts-19, ts-29, ts-46, and ts-112) expression levels were responsive to the RUNX1 tumor suppressor expression and that ts-112 was inversely correlated with RUNX1 and possessed oncogenic activity. This finding suggests that expression of some type II tsRNAs might be regulated by tumor-suppressor genes or oncogenes, which could also explain differential expression of tsRNAs in cancer cells.…”
Section: Tsrnas As Biomarkers In Human Diseasementioning
confidence: 99%
“…57 The regulation of type II tsRNA biogenesis has only recently started to be revealed. Farina et al 58 determined that four type II tsRNAs (ts-19, ts-29, ts-46, and ts-112) expression levels were responsive to the RUNX1 tumor suppressor expression and that ts-112 was inversely correlated with RUNX1 and possessed oncogenic activity. This finding suggests that expression of some type II tsRNAs might be regulated by tumor-suppressor genes or oncogenes, which could also explain differential expression of tsRNAs in cancer cells.…”
Section: Tsrnas As Biomarkers In Human Diseasementioning
confidence: 99%
“…71 Researchers have found that runt-related transcription factor 1 (RUNX1) may prevent the excessive malignant proliferation of breast cancer epithelial cells by inhibiting the carcinogenesis of ts-112, thereby enhancing its role in maintaining the healthy function of breast epithelial cells. 72 Researchers have used RNA-seq to analyze the expression levels of tRF in normal prostate tissues adjacent to prostate cancer tissues and with cells from tissues at different stages of prostate cancer, and found 598 differentially expressed tRFs. 73 In recurrent prostate cancer, the tRF from tRNA Phe-GAA was significantly downregulated compared with that of the adjacent normal tissue, while the tRF from tRNA Lys-CTT was upregulated and expressed at higher levels in higher grade prostate cancer, and the patients with highly expressed tRF based on tRNA Lys-CTT /tRNA Phe-GAA had shorter survival and recurrence periods.…”
Section: Roles Of Trfs and Tirnas In Human Diseases Cancersmentioning
confidence: 99%
“…Similarly, 5′-SHOT-RNA can also enhance cell proliferation in BC cells [66]. Inhibition of ts-112, the expression of which is regulated by the tumor suppressor runt-related transcription factor 1 (RUNX1), can reduce the proliferative capacity of aggressive breast cancer cells while its overexpression promotes cell growth in normal-like mammary epithelial cells [67].…”
Section: Breast Cancermentioning
confidence: 99%